Cost-Effectiveness of Offering Contraceptives to Incarcerated Women Prior to Release from Prison [20F]. (May 2018) - Toffey, David E.; Allen, Allison; Caughey, Aaron B.
Abstract : INTRODUCTION: Incarcerated women face numerous barriers to consistent and affordable contraception, and experience high rates of unintended pregnancy with associated individual, institutional, and societal costs. We sought to determine the benefits of providing contraceptive services to this high-risk patient population. METHODS: A decision-analytic model using TreeAge software was designed to compare offering contraceptive counseling and methods prior to release from prison with providing no such services. Our study included long- and short-acting reversible contraception methods and included rates of discontinuation and method switching. All probabilities and utilities were derived from the literature. Utilities were included with a discounted life expectancy rate of 3% to produce quality adjusted life years (QALYs). The cost-effectiveness threshold was set at $100, 000 per QALY. Outcomes include unintended pregnancies, ectopic pregnancy, spontaneous and therapeutic abortion, and preterm and term births. RESULTS: Offering contraception prior to release is cost-effective for all methods assessed. In a theoretical cohort of 56, 000 incarcerated women of reproductive age not intending to get pregnant over a 12-month interval, offering contraception would prevent 18, 251 unintended pregnancies, 644 preterm births, 6, 045 term births, 180 ectopic pregnancies, 8, 310 therapeutic abortions, and save $85 million. Sensitivity analysis demonstrated cost-effectiveness when services are utilized at a rate 25% of that modeled based on reported rates. Additionally, these services are cost-saving up to 9-times the costs modeled for counseling and office visits, and cost-effective up to 32-times these costs. CONCLUSION: Offering incarcerated reproductive-age women contraception prior to release is cost-effective, cost-saving, and reduces the rate of unintended pregnancy and associated obstetric complications.